Creamed Coconut Testa and Creamed Coconut as Substitutes for Coconut Milk in Culinary Uses - Kumari, K. G. S. N.; Ulpathakumbura, B. S. K.; Gunarathna, K. M. R. U.; Lai, Oi Ming; Marikkar, J. M. N. (International Coconut Community, 2024)
Coconut milk plays a crucial role in preparation ofcurries and other savoury dishes in Sri Lanka.While squeezing grated coconut manually, there is a wastage ofcoconut as well as coconut testa which is a significant by-product of coconut processing industries. This study aimed to evaluate the potential of utilizing creamed coconut (CC) and creamed coconut testa (CCT) as a viable substitute for coconut milk in culinary uses. To attain this objective, the nutritional composition ofCC and CCT was determined and sensory evaluation was undertaken to test the suitability of these two products as cooking medium on a potato curry using a group of thirty semi-trained panelists. Four formulations of CCT incorporated potato curry were prepared coded as F₁ (CCT:water = 1:9), F₂ (CCT:water =1:4), F₃ (CCT:water = 3:7) and F₄ (CCT:water = 2:3). Besides, P₁ (CC:water = 1:9), P₂ (CC:water = 1:4), P₃ (CC:water = 3:7), P₄ (CC:water = 2:3) were coded as the four formulations of potato curry, incorporating CC. The analysis revealed that fat, crude protein and carbohydrate in CC was higher than CCT except crude fiber content. However, there was no significant (p > 0.05) difference in ash and moisture contents. According to sensory evaluation, F₁ (CC:water = 1:9) and P₂ (CC:water = 1:4) were identified as the most preferred potato curry formulations incorporating CCT and CC respectively. In conclusion, there was a potential ofutilizing and maximizing coconut meat and testa as a viable substitute for coconut milk in culinary applications.